SwissBioPics—an interactive library of cell images for the visualization of subcellular location data. (12th April 2022) - Le Mercier, Philippe; Bolleman, Jerven; de Castro, Edouard; Gasteiger, Elisabeth; Bansal, Parit; Auchincloss, Andrea H; Boutet, Emmanuel; Breuza, Lionel; Casals-Casas, Cristina; Estreicher, Anne; Feuermann, Marc; Lieberherr, Damien; et al.
Abstract: SwissBioPics (www.swissbiopics.org ) is a freely available resource of interactive, high-resolution cell images designed for the visualization of subcellular location data. SwissBioPics provides images describing cell types from all kingdoms of life—from the specialized muscle, neuronal and epithelial cells of animals, to the rods, cocci, clubs and spirals of prokaryotes. All cell images in SwissBioPics are drawn in Scalable Vector Graphics (SVG), with each subcellular location tagged with a unique identifier from the controlled vocabulary of subcellular locations and organelles of UniProt (https://www.uniprot.org/locations/ ). Users can search and explore SwissBioPics cell images through our website, which provides a platform for users to learn more about how cells are organized. A web component allows developers to embed SwissBioPics images in their own websites, using the associated JavaScript and a styling template, and to highlight subcellular locations and organelles by simply providing the web component with the appropriate identifier(s) from the UniProt-controlled vocabulary or the 'Cellular Component' branch of the Gene Ontology (www.geneontology.org ), as well as an organism identifier from the National Center for Biotechnology Information taxonomy (https://www.ncbi.nlm.nih.gov/taxonomy ). The UniProt website now uses SwissBioPics to visualize the subcellular locations and organelles where proteins function. SwissBioPics is freely available for anyone to use under a Creative Commons Attribution 4.0 International (CC BY 4.0) license. Database URL: www.swissbiopics.org